2021
DOI: 10.1371/journal.pone.0247986
|View full text |Cite
|
Sign up to set email alerts
|

A decade of theory as reflected in Psychological Science (2009–2019)

Abstract: The dominant belief is that science progresses by testing theories and moving towards theoretical consensus. While it’s implicitly assumed that psychology operates in this manner, critical discussions claim that the field suffers from a lack of cumulative theory. To examine this paradox, we analysed research published in Psychological Science from 2009–2019 (N = 2,225). We found mention of 359 theories in-text, most were referred to only once. Only 53.66% of all manuscripts included the word theory, and only 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
(25 reference statements)
1
37
0
Order By: Relevance
“…Future researchers in PP and postdisciplinary studies can explore what the state of the art is for them as being conducted in psychology and other disciplines. For example, McPhetres et al (2021) found in an analysis of articles in a flagship psychology journal that the word "theory" only appears in round about half of all manuscripts, and that only 15.33% of manuscripts indicated that it is about testing of theories. They concluded that the majority of studies are not theory-driven and can thus not contribute to cumulative growth in theories.…”
Section: Theory and Methods Embedded In Meta-assumptionsmentioning
confidence: 99%
“…Future researchers in PP and postdisciplinary studies can explore what the state of the art is for them as being conducted in psychology and other disciplines. For example, McPhetres et al (2021) found in an analysis of articles in a flagship psychology journal that the word "theory" only appears in round about half of all manuscripts, and that only 15.33% of manuscripts indicated that it is about testing of theories. They concluded that the majority of studies are not theory-driven and can thus not contribute to cumulative growth in theories.…”
Section: Theory and Methods Embedded In Meta-assumptionsmentioning
confidence: 99%
“…By describing how, and in some cases why, phenomena occur in the world, theories productively organize empirical literature, differentiating promising from not-sopromising directions for future research that would otherwise be difficult to discern without theory (McPhetres et al, 2021;Szollsi & Donkin, 2021). Theories have two predominant aspects: description and explanation, with individual theories varying in their emphasis on each (McGann & Speelman, 2020).…”
Section: What Is Theory and How Is It Developed Evaluated And Integra...mentioning
confidence: 99%
“…Yet, theory development has been relatively underscrutinized compared to the field's focus on methods (Fielder, 2017;Wentzel, 2021). Scholars who have looked deeply at psychology's use of theory have lamented the paucity of clear descriptions of theory development (Eronen & Bringmann, 2021), the scarcity of clear connections between theory and the empirical work published in psychology journals, (McPhetres et al, 2021), the difficulty in evaluating the adequacy of theories (Gervais, 2021), the oftenunchecked proliferation of multiple seemingly similar theories about the same phenomena (Eronen & Romeihn, 2020;Mischel, 2008), and the inequitable prominence of WEIRD (i.e., Western, educated, industrialized, rich, and democratic;Henrich et al, 2010) and able-ist (Emery & Anderman, 2020) perspectives in psychology scholarship. Quite simply, more just, effective, reliable, and beneficial psychology scholarship and practice requires reform focused not just on methods and anti-racist practices, but also on theory development and use.…”
mentioning
confidence: 99%
“…An integral part of science is testing theories. Many papers in the social sciences are phrased as attempts to test theories (though see McPhetres et al, 2020). A key inferential tool used for this purpose is statistics, and in particular significance testing.…”
mentioning
confidence: 99%